Avaliação educacional e a formação de professores em Educação Física: uma análise nas instituições privadas de ensino superior - Poleto, Fabia Maria Boreli (2020)
This dissertation aimed to understand how educational assessment has been prescribed in teacher education courses in Physical Education at private institutions in the State of Espírito Santo. It is organized in three chapters that dialogue with each other